Kalmusia variispora as a new Grapevine Trunk Disease pathogen record in Cyprus - Makris, Georgios (My University, 2023)
Grapevine trunk diseases (GTDs) form an aggregate of fungal origin that is currently considered the most destructive biotic factor of grapevines globally. Beyond the well-known fungal pathogens, recent studies have increased our knowledge regarding new, wood-colonizing fungal species that are associated with GTDs. During a survey conducted between 2017-2018 in Cyprus vineyards to investigate the causal agents of GTDs, the occurrence of a relatively new GTD pathogen, Kalmusia variispora was recorded. Detailed species identification was supported by morphology and multilocus phylogenetic analysis of six different loci (ITS, LSU, SSU, b-tub, tef1-α and rpb2). The pathogenicity of representative K. variispora isolates was carried out on lignified stems of two-year-old potted grapevines under field conditions for an incubation period of 12 months. All isolates were pathogenic, causing dark brown to black discoloration, extending both ways from the inoculation point. Since wood necrosis in GTDs is caused by fungal digestive exoenzymes we also examined the in vitro potential of K. variispora to produce cellulases, pectinases, laccases, and amylases. All tested isolates exhibited cellulase and pectinase activity, while none of them showed amylolytic activity. However, there were observed differences in the laccase secretion among isolates. To the best of our knowledge this is the first record of K. variispora associated with GTDs in Cyprus and one of a few worldwide.
Keywords: Cyprus; grapevine trunk diseases; Kalmusia variispora; Vitis vinifera; Didymosphaeriaceae; Κύπρος; ασθένειες του ξύλου της αμπέλου